Online Analysis System of Application of Partners for Land Asrocument Officers of Sukoharjo District - Laidestifre Putri Santoso; Muqorobin Muqorobin; Fatkhurrochman Fatkhurrochman (International Journal of Computer and Information System (IJCIS), 2020)
Research in the writing of this final assignment takes the title Analysis of the Online Sale and Purchase Deed Registration System Application for Sukoharjo District Land Deed Maker Officers, where the PPAT itself consists of leaders and office and field staff who bring files to the ATR / BPN office in Sukoharjo, this research applies the method UML (Unified Model Language), in the process. This is to find out the constraints of PPAT in examining the registration of land sale and purchase deeds in the Sukoharjo regency. The data that was collected were processed qualitatively and analyzed descriptively and analytically. The results showed; 1) The function of registering via PPAT Online in assisting PPAT in the transfer of land rights in Sukoharjo Regency is to assist in the process of changing names that arise from the seller to the buyer. 2) The juridical consequences if both parties do not fulfill obligations such as taxation in making deed of transfer of land rights, namely that PPAT will not process the transfer of rights to land and / or buildings if it is not equipped with proof of payment of BPHTB and PPh taxes so that the consequences.